THE IMPLEMENTATION OF WEBGIS TO SHOW THE SPREAD OF HALAL CUISINE SPOTS IN MEDAN - Aulia Pratama Tambunan; Samsudin Samsudin; Septiana Dewi Andriana (JISTech (Journal of Islamic Science and Technology), 2019)
Halal food is one of the obligations for Muslims that must be carried out and obeyed. Medan is one of the culinary cities in Indonesia and often called as the paradise of culinary, not only traditional cuisine, Medan also serves culinary delights from various parts of the world, from Asian food to Western food. However, not all culinary in Medan is registered as halal food, therefore a system that can manage the data of halal food in Medan is needed. WebGis is a computer-based system that has the ability to handle spatial and non-spatial data. This system is built using Google Maps API as a tool to determine the distribution of halal cuisine spots in Medan. The WebGis of the distribution of halal cuisine spots in Medan presents spatial and non-spatial information about the distribution. This system also provides information about halal cuisine that has been registered in the system that has been built.